2019
DOI: 10.3390/app9153115
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Angle of Curvature of the Spine and SEMG Amplitude of the Erector Spinae in Young School-Children

Abstract: The aim of the study was to analyze the relationship between the angle of spinal curvature and surface electromyography (SEMG) amplitude of the erector spinae in young school-children. A total of 251 children aged 7–8 participated in the study. The analysis involved 103 (41%) children with scoliosis, 141 (56.17%) with scoliotic posture, and seven (3.0%) with normal posture. Body posture was evaluated using the Diers formetric III 4D optoelectronic method. Analysis of SEMG amplitude of the erector spinae was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…In addition, asymmetry in paraspinal muscle activities is observed in adolescent idiopathic scoliosis (AIS) [ 4 8 ]. Specifically, the angle of spinal curvature significantly correlated with the surface electromyography (sEMG) amplitude of the erector spinae in young school children [ 9 ]. Kwok et al [ 7 ] compared paraspinal muscle activities between female adolescents with and without mild scoliosis (i.e., spinal curve angle less than 20°) by sEMG during habitual standing and sitting postures and found that those with thoracic- or thoracolumbar-type scoliosis had higher average root-mean-square (RMS) sEMG values on the convex side of the affected muscle regions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, asymmetry in paraspinal muscle activities is observed in adolescent idiopathic scoliosis (AIS) [ 4 8 ]. Specifically, the angle of spinal curvature significantly correlated with the surface electromyography (sEMG) amplitude of the erector spinae in young school children [ 9 ]. Kwok et al [ 7 ] compared paraspinal muscle activities between female adolescents with and without mild scoliosis (i.e., spinal curve angle less than 20°) by sEMG during habitual standing and sitting postures and found that those with thoracic- or thoracolumbar-type scoliosis had higher average root-mean-square (RMS) sEMG values on the convex side of the affected muscle regions.…”
Section: Introductionmentioning
confidence: 99%
“…This asymmetry is more prevalent in LBP patients, inducing a unilateral pathological activation of the lumbar musculature [12]. Wilczyński et al found significant correlations between increased ES neuromuscular activity and the Cobb angle of scoliotic postural change [36]. They conclude from their results that idiopathic scoliosis frequently is the consequence of an asymmetrically increased muscle tone of the ES.…”
Section: Discussionmentioning
confidence: 99%
“…This asymmetry is more prevalent in LBP patients, inducing a unilateral pathological activation of the lumbar musculature [ 12 ]. Wilczyński et al found significant correlations between increased ES neuromuscular activity and the Cobb angle of scoliotic postural change [ 43 ]. They conclude from their results that idiopathic scoliosis is frequently the consequence of an asymmetrically increased muscle tone of the ES.…”
Section: Discussionmentioning
confidence: 99%